Development of a high performance batteries charger with low THD, high power factor, and high efficiency (2018)
This paper presents the design, simulation, and implementation of an off-board charger of medium and low capacity batteries that incorporates a power factor corrector, reaches a low THD current with the advantage of providing higher robustness against network frequency variations, and allows the implementation of three different charging strategies. On the one hand, this charger consists of a galvanic isolation stage, followed by a bridge rectifier connected to a Boost converter, which regulates the power factor and THD. On the other hand, a Buck converter cascaded with the Boost serves as a current or voltage source, depending on the operating charging strategy. Subsequently, results obtained in the testing phase are presented, placing great emphasis on obtaining a power factor of 0.978 and a THD of 5.7%, which are compared to standard IEC 61000-3-2. Finally, the efficiency of the prototype, which reaches a maximum of 91.1%, is evaluated; conclusions are therefore presented.